Interpretation of visual arts across societies and political culture emerging research and opportunities - Merviö, Mika Markus 1961- (Advances in religious and cultural studies (ARCS) book series, 2017)
"This book provides a very personal interpretation of art and politics. It discusses the changing role of art and interpretations of art in contemporary societies. Highlighting a range of multidisciplinary topics such as diversity, propaganda, and culture wars"...